2010
DOI: 10.1093/eurheartj/ehq296
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of arterial stiffness and early mild diastolic heart failure in general middle and aged population

Abstract: The increased arterial stiffness is associated with early mild DHF in a general middle and aged population independently of age, male gender, BMI, PVWT, IVST, E/E' ratio, LVMI, and high blood pressure. The non-invasive techniques described may allow serial measurements to be made over time to monitor baPWV changes in arteries provided the introduction of anti-arteriosclerosis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 42 publications
4
52
3
Order By: Relevance
“…Although in elderly patients and patients with hypertension LV hypertrophy, 5 BP, 23 and arterial stiffness 24 are major factors leading to diastolic dysfunction and subsequently to HF with preserved EF, in our AO asymptomatic subjects, we could show that increased LV mass and diastolic dysfunction could be detected early, before LV hypertrophy, hypertension, and arterial stiffening can be diagnosed. Furthermore, increased collagen type III turnover was observed in the study participants with diastolic dysfunction.…”
Section: Cardiac and Arterial Remodeling: Changes In Structure And Fucontrasting
confidence: 49%
“…Although in elderly patients and patients with hypertension LV hypertrophy, 5 BP, 23 and arterial stiffness 24 are major factors leading to diastolic dysfunction and subsequently to HF with preserved EF, in our AO asymptomatic subjects, we could show that increased LV mass and diastolic dysfunction could be detected early, before LV hypertrophy, hypertension, and arterial stiffening can be diagnosed. Furthermore, increased collagen type III turnover was observed in the study participants with diastolic dysfunction.…”
Section: Cardiac and Arterial Remodeling: Changes In Structure And Fucontrasting
confidence: 49%
“…40 Mechanisms explaining its predictive value can be inferred by its associations with arterial and overall CV performance. baEI is associated with left ventricular function, 41 left ventricular hypertrophy, 6,42 and impaired coronary perfusion. 43 Furthermore, baEI is an independent predictor of longitudinal increases in BP, as well as of new onset of hypertension and microalbuminuria.…”
Section: Baei: Clinical Implicationsmentioning
confidence: 99%
“…This type of heart failure often occurs in patients who have previously suffered myocardial infarction ). The relationship of arterial stiffness to LV function has been studied for heart failure with preserved EF to elucidate the contribution of arterial stiffness to onset of heart failure with preserved EF (Desai et al 2009;Kang et al 2010). Some previous studies demonstrated the relationship between arterial stiffness and LV function by measuring pulse wave velocity (Tsioufis et al 2005;).…”
mentioning
confidence: 99%